Answer:X=16
Step-by-step explanation:
first you divide -2 ,to -2x and also divide -32 by -2 and you get x=16
Hope this helped!!!
Using the factor theorem, it is found that the polynomial is:
![f(x) = x^3 - 2x^2 - 3x + 6](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E3%20-%202x%5E2%20-%203x%20%2B%206)
Given by the first option
---------------------------
Given a polynomial f(x), this polynomial has roots
using the factor theorem it can be written as:
, in which a is the leading coefficient.
---------------------------
In this question:
![x_1 = 2](https://tex.z-dn.net/?f=x_1%20%3D%202)
![x_2 = \sqrt{3}](https://tex.z-dn.net/?f=x_2%20%3D%20%5Csqrt%7B3%7D)
![x_3 = -\sqrt{3}](https://tex.z-dn.net/?f=x_3%20%3D%20-%5Csqrt%7B3%7D)
- By the options, leading coefficient
![a = 1](https://tex.z-dn.net/?f=a%20%3D%201)
Thus:
![f(x) = (x - 2)(x - \sqrt{3})(x + \sqrt{3})](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x%20-%202%29%28x%20-%20%5Csqrt%7B3%7D%29%28x%20%2B%20%5Csqrt%7B3%7D%29)
![f(x) = (x - 2)(x^2 - 3)](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x%20-%202%29%28x%5E2%20-%203%29)
![f(x) = x^3 -2x^2 - 3x + 6](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E3%20-2x%5E2%20-%203x%20%2B%206)
Which is the polynomial.
A similar problem is given that: brainly.com/question/4786502
Given that quadrilateral QRST is a square.
Each angle of a square is of 90 degrees.
Angle <RQT is also an angle of 90 degrees.
We also given angle RQT = 3x - 6.
So, we can setup an equation as 3x-6 =90.
Now, we need to solve the equation for x.
6 is being subtracted from left side.
We always apply reverse operation. Reverse operation of subtraction is addition.
So, adding 6 on both sides of the equation, we get
3x-6+6 =90+6.
3x = 96.
3 is being multipied with x, in order to remove that 3, we need to apply reverse operation of multiplication.
So, dividing both sides by 3.
![\frac{3x}{3} = \frac{96}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%7D%7B3%7D%20%3D%20%5Cfrac%7B96%7D%7B3%7D)
x=32 (final answer).
Answer:
-9x^5(x+3)(x-7)
Step-by-step explanation:
factor out -9x^3 from the expression